A Transcriptomic Analysis of Stylo [Stylosanthes guianensis (Aubl.) Sw.] Provides Novel Insights Into the Basis of Salinity Tolerance - Liu, Yiming; Kong, Danyu; Yang, Hubiao; Douxchamps, Sabine; Atieno, Mary; Xu, Bin; Wang, Wenqiang; Liu, Guodao (Frontiers in Sustainable Food Systems, 2022)
Tropical areas have large distribution of saline soils and tidal flats with high salinity level. Salinity stress is a key factor limiting widespread use for tropical forage such as stylo. This study was designed to screening salinity tolerant of 84 S. guianensisi accessions, plants were subjected to Hoagland solution or Hoagland solution with 200 mM NaCl for up to 15 d in green house, salinity tolerant CIAT11365 and salinity sensitive FM05-2 were obtained based on WLR. Further verification of salinity tolerant in CIAT11365 and FM05-2 with different salinity gradient showed that, salinity stress increased WLR, decreased SPAD, Fv/Fm and Pn in FM05-2, but CIAT11365 exhibited lower WLR, higher SPAD, Fv/Fm and Pn. Leaf RNA-Seq revealed that plasma membrane and vacuolar membrane transporter such as cation/H+ antiporter, Ca2+ transmembrane transport, annexin, nodulin MtN21/EamA-like transporter, plant hormones such as Auxin increase and Cytokinin inhibition may play key roles in CIAT11365 response to salinity stress. The results of this study may contribute to our understanding the molecular mechanism underlying the responses of S. guianensisi to salinity stress, and also provide important clues for further study and in-depth characterization of salinity-resistance breeding candidate genes in S. guianensisi.